2017
DOI: 10.1186/s13059-017-1220-4
|View full text |Cite
|
Sign up to set email alerts
|

Easi-CRISPR: a robust method for one-step generation of mice carrying conditional and insertion alleles using long ssDNA donors and CRISPR ribonucleoproteins

Abstract: BackgroundConditional knockout mice and transgenic mice expressing recombinases, reporters, and inducible transcriptional activators are key for many genetic studies and comprise over 90% of mouse models created. Conditional knockout mice are generated using labor-intensive methods of homologous recombination in embryonic stem cells and are available for only ~25% of all mouse genes. Transgenic mice generated by random genomic insertion approaches pose problems of unreliable expression, and thus there is a nee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
411
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(448 citation statements)
references
References 57 publications
10
411
1
1
Order By: Relevance
“…Therefore, zygote injection of Cas9 protein instead of the mRNA may help to reduce mosaicism in founders [21], because Cas9 protein-RNA complex is more likely to degrade rapidly, leading to a shorter half-life than Cas9 mRNA [24][25][26][27]. The results from some recent studies support such reasoning [18][19][20]26].…”
Section: Crispr/cas9 Components: Cas9supporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, zygote injection of Cas9 protein instead of the mRNA may help to reduce mosaicism in founders [21], because Cas9 protein-RNA complex is more likely to degrade rapidly, leading to a shorter half-life than Cas9 mRNA [24][25][26][27]. The results from some recent studies support such reasoning [18][19][20]26].…”
Section: Crispr/cas9 Components: Cas9supporting
confidence: 74%
“…Unlike sgRNA, in dual-crRNA:tracrRNA, crRNA and tracrRNA are synthesized separately, and then annealed together to be used as the guide RNA [15,18,19]. Recently, a few reports have demonstrated that a dual-crRNA:tracrRNA combined with Cas9 protein can increase the eiciency of genome editing, especially the frequency of HDR [18][19][20]. Therefore, dual-crRNA:tracrRNA should still be considered when planning chromosome rearrangement projects.…”
Section: Crispr/cas9 Components: Guide Rnamentioning
confidence: 99%
“…SSOs alone have demonstrated efficiencies ranging from 10 −5 to 2% in mammalian cells (Table 1) 3335 . However, the most prevalent utility of SSOs are in conjunction with a designer nuclease to generate much higher rates of modification 5,36 .…”
Section: Genome Editing Systems — Not Just Cas9mentioning
confidence: 99%
“…Similarly, Dr. Rolf Turk from Integrated DNA Technologies (IDT) talked about the insertion of targeted repair template for the generation of knock-in strains or animal models, including insertion of reporter genes or specific mutations. As an evident, when the repair template consists of double-stranded DNA, the knock-in efficiency is usually very low [26]. Therefore, to overcome this low knock-in frequency, the use of single-stranded oligonucleotides could be an alternative as HDR templates.…”
Section: Genome-editing-based Nanomedicinesmentioning
confidence: 99%
“…However, the generation of specific disease models in animals that recapitulate the biological and clinical characteristics of humans by targeting specific locus in the genome has made CRISPR-Cas system an essential subject for studying various diseases [29]. Dr. Channabasavaiah Gurumurthy from UNMC, introduced Easi- CRISPR ( E fficient a dditions with s sDNA i nserts-CRISPR), a strategy of using long single-stranded DNA as a donor template to solve the major issues related to animal genome engineering by the inefficiency of targeted DNA cassette insertion [26]. Per.…”
Section: Genome-editing-based Nanomedicinesmentioning
confidence: 99%